Cut-off lows in the Southern Hemisphere: climatology, structure and energetics - Henri Rossi Pinheiro (2018)
Annually, subtropical regions are exposed to stormy conditions caused by mid-upper level cold lows, known as Cut-off Lows (COLs), a weather system that bring heavy rainfall and flooding in different parts of the world. It is therefore very important to understand where and how COLs form, and which factors control their development. In this thesis, the objective tracking algorithm, TRACK, is used with different methodologies to study the COLs in the Southern Hemisphere (SH) with the focus on their climatology, structure and energetics. The hemispheric distribution of COLs is obtained by using both vorticity and geopotential at 300 hPa. This analysis confirms that the peak activity occurs around the main continents: Australia, South America and southern Africa. A comparison of COLs between five different reanalysis products indicates significant improvements in the agreement between the newer reanalyses ERAI, NCEP-CFSR, MERRA-2, and JRA-55 compared to the older JRA-25, particularly with respect to location and intensity. Different features of the threedimensional structure of COLs are identified through the composites of the strongest systems, such as the symmetrical circulation at upper levels and the baroclinic zones across the edges of the cold core (400-500 hPa) and the warm core (~100 hPa). Results indicate that the upper-level fronts propagate downstream throughout the COL life cycle. As a result of the COL formation, large amounts of stratospheric air are introduced into the troposphere, modifying the vertical distribution of potential vorticity and ozone. The precipitation in COLs varies widely according to the life cycle, reaching a peak 24 hours after the maximum intensity in vorticity. There is a clear association between the medium and high cloud cover and precipitation, where maximum values are found east of the COL centre due to moist uplift at middle levels and strong divergence at upper levels. The possible link between intensity/moisture and precipitation associated with COLs suggests that moisture is important for controlling the areal coverage of precipitation, while intensity affects the magnitude of precipitation. The largest precipitation zones are found for the summer and autumn COLs, though winter and spring have the strongest COLs. Results confirm earlier findings that deeper COLs cause more precipitation than shallower COLs. A new method is proposed to estimate the COL vertical depth, indicating that COLs are relatively deep in Australia and southwestern Pacific, where more than 30% of the total number extend vertically toward the surface. A similar structure was found for the COLs occurring east of the Andes, where the mountain effect may contribute to the COL deepening, and the moisture and heat transport from the Amazon region increasing the precipitation. The ageostrophic flux convergence (AFC) together with the baroclinic (BRC) conversion are found to be the primary mechanisms for the COL development. The AFC is important for the formation and intensification of the COL, while the BRC conversion is important to maintain the system. The dissipation of the COLs occurs due to dispersive fluxes together with other processes such as friction and latent heat release. The barotropic (BRT) conversion act to transfer Eddy kinetic energy to zonal flow kinetic energy during the growth phase, but this is not enough to prevent the COL intensification. Results show that the COLs originating in the lee side of the Andes are deeper due to local effects, which enhance the vertical motion and the system is intensified mostly due to BRC conversion.